FINANCIAL PERFORMANCE ANALYSIS OF PT MITRA ADIPERKASA TBK BEFORE AND DURING PANDEMIC COVID-19 - Ali, Kresnanda
The study begins with a detailed background, highlighting the significant impact of the pandemic on the company's financial performance, particularly the drastic decrease in net profit margin in 2020 compared to 2019 due to the government's implementation of regulations to address the pandemic, such as PSBB and PPKM. This study aims to analyze and provide insights into the financial performance of PT Mitra Adiperkasa TBK during the COVID-19 pandemic and contribute to the existing literature on financial performance analysis. The research objectives are focusing on the need to analyze the company's financial performance before and during the pandemic, and the methods employed include quantitative analysis using financial report data from PT Mitra Adiperkasa TBK, utilizing ratio analysis, vertical analysis, and horizontal analysis. The findings of the study are presented in the results and discussion section, which includes a detailed analysis of the company's horizontal analysis for different periods, comparative analysis, vertical analysis, and ratio analysis. Furthermore, provides a comprehensive overview of the company's financial performance, including the impact of the pandemic on key financial indicators such as net income, sales revenue, total assets, total equity, and total liabilities. The implications of the findings are significant, the Covid-19 pandemic significantly impacted MAP, particularly in 2020, evident in the sharp decline in net income and various financial ratios. The study's theoretical foundation, literature review, and detailed analysis contribute to the existing body of knowledge on financial performance analysis, making it a valuable resource for researchers and practitioners in the field.